Physical characteristics for drying effect of using far-infrared dryer on Aquilaria Malaccensis leaves: article - Mohd Zain, Nurul Shazana; Alwi, Habsah (2017)
Food, vegetables and seeds usually associate with drying kinetics but none of them were using Aquilaria Malaccensis leaves. Until now, there were no journals or articles on the study of Aquilaria Malaccensis leaves on the drying kinetics and the behaviour of the leaves. The objectives of this research were to investigate the effect of drying at temperature range from 40, 50 and 60°C. Besides that, the color, moisture content and the elements of the leaves after drying in far-infrared dryer were examined because to find the most optimum condition for the leaves. The data for each temperature were calculated and were compared by using graph between these temperatures. The drying kinetics of (Aquilaria Malaccensis) leaves was investigated at different far-infrared drying temperature (40, 50 and 60°C). Besides that, the drying rate of the leaves were shown to be the most optimum conditions at 60°C, compared to other temperatures because it had the fastest time to be constants. The color measurements data shown that at 60°C, the brightness and the chroma were the highest. In the other hand, the hue angles were the highest for 60°C when the time strikes at 100 minutes. In summarize the most optimum conditions for the leaves for drying kinetics under far-infrared dryer were at 60°C.